Co‐evolutionary patterns and diversification of ant–fungus associations in the asexual fungus‐farming ant Mycocepurus smithii in Panama. (3rd May 2013) - Kellner, K.; Fernández‐Marín, H.; Ishak, H. D.; Sen, R.; Linksvayer, T. A.; Mueller, U. G.
Abstract Partner fidelity through vertical symbiont transmission is thought to be the primary mechanism stabilizing cooperation in the mutualism between fungus‐farming (attine) ants and their cultivated fungal symbionts. An alternate or additional mechanism could be adaptive partner or symbiont choice mediating horizontal cultivar transmission or de novo domestication of free‐living fungi. Using microsatellite genotyping for the attine ant Mycocepurus smithii and ITS rDNA sequencing for fungal cultivars, we provide the first detailed population genetic analysis of local ant–fungus associations to test for the relative importance of vertical vs. horizontal transmission in a single attine species. M. smithii is the only known asexual attine ant, and it is furthermore exceptional because it cultivates a far greater cultivar diversity than any other attine ant. Cultivar switching could permit the ants to re‐acquire cultivars after garden loss, to purge inferior cultivars that are locally mal‐adapted or that accumulated deleterious mutations under long‐term asexuality. Compared to other attine ants, symbiont choice and local adaptation of ant–fungus combinations may play a more important role than partner‐fidelity feedback in the co‐evolutionary process of M. smithii and its fungal symbionts.